Studi Kasus Implementasi Service Oriented Architecture (SOA) di Credit Suisse - Sartika Kurniali (Bina Nusantara University, 2013)
Credit Suisse Group (CSG) is a leading company engaged in global financial services. At the end of 90s IT infrastructure complexity of Credit Suisse has reached a critical situation. The existing IT infrastructure is no longer able to support the required business functionality. This leads to the introduction of an integrated architecture based on Service-Oriented Architecture (SOA). The purpose of this study is to learn how Credit Suisse successfully implements SOA both on a technical and organizational level. Analyses were performed by processing factual and reference data acquired. From the research, the successful implementation is due to clarity of interface, clarity of process, management commitment, and solid technology. Their success does not come easily since they also face obstacles and conflicts on the implementation.